Designing museums as cross-cultural contact zones: the Narrative-oriented Metaphor from the inside-out - Zheng, Chunhui (2021)
The “Belt and Road Initiative” (B&R for short) is an essential pillar of the Chinese “going out” and “bringing in” diplomatic strategy proposed by President Xi Jinping in 2013. It was called the most significant regional cooperation platform at present due to its impact on international relations. On the one hand, it can promote the economic prosperity and regional cooperation of countries participating in B&R. On the other hand, it can provide an inclusive platform for cultural exchanges and mutual learning between each country. As most of the programs and projects are government-to-government, it is necessary to find a way to communicate with the public to achieve people-to-people bonds. For cross-cultural communication, this research focuses on the museums, especially the cultural-historical museums that contain and share many memories and stories along the Silk Roads1 throughout history. Scholars have explored the idea that museums serve as educational institutions during the last decades. The museum is still considered a didactic institution in China and aims at collection display. This study claims that the museums in B&R are cross-cultural contact zones. 2 So museum design emphasises communication in a way that is highly interpretable by visitors from different cultural backgrounds. Based on this research background, the author explores the narrative – as the common attribute of architecture and exhibition language, and more importantly, how to convey it through the architect’s discourse. In particular, the author examines how a cross-cultural museum is an ideal place for visitor’s communication.The current researches on the museum usually separate the architectural language from the museum studies. Although narrative has been applied in exhibition design and architectural design, respectively, there is still a gap. To fill this gap, the author claims narrative-oriented design for cultural-historical museums in B&R. And how the architect’s discourse can enhance the transmission of museum narrative. The desired outcome of this research is to propose a design guideline for architects, especially Chinese architects if they have the opportunity to design museums in B&R countries. Moreover, the findings of this study could support cross-cultural communication and the identity of museums under the B&R background. To explore the questions, the author reviewed the theoretical framework of structuralist linguistics and semiotics as the foundation of architectural language. Then, the author proposed the narrative-oriented metaphor as a design approach to link the architecture to social and narrative context. The case studies of the Mary Rose Museum and the Ashmolean Museum aims to examine its improvement on visitor’s accessibilities. Keywords: B&R Initiative; narrative-oriented design; from the inside-out; cross-cultural contact zone; metaphorical expression; conceptual cognition.